Activity of Estafietin and Analogues on Trypanosoma cruzi and Leishmania braziliensis - Sülsen, Valeria P. (Molecules, 2019)
Sesquiterpene lactones are naturally occurring compounds mainly found in the Asteraceae family. These types of plant metabolites display a wide range of biological activities, including antiprotozoal activity and are considered interesting structures for drug discovery. Four derivatives were synthesized from estafietin (1), isolated from Stevia alpina (Asteraceae): 11βH,13-dihydroestafietin (2), epoxyestafietin (3a and 3b), 11βH,13-methoxyestafietin, (4) and 11βH,13-cianoestafietin. The antiprotozoal activity against Trypanosoma cruzi and Leishmania braziliensis of these compounds was evaluated. Epoxyestafietin was the most active compound against T. cruzi trypomastigotes and amastigotes (IC(50) values of 18.7 and 2.0 µg/mL, respectively). Estafietin (1) and 11βH,13-dihydroestafietin (2) were the most active and selective compounds on L. braziliensis promastigotes (IC(50) values of 1.0 and 1.3 μg/mL, respectively). The antiparasitic activity demonstrated by estafietin and some of its derivatives make them promising candidates for the development of effective compounds for the treatment of Chagas disease and leihsmaniasis.